Engineering osteochondral constructs through spatial regulation of endochondral ossification. - KELLY, DANIEL; BUCKLEY, CONOR (My University, 2013)
Chondrogenically primed bone marrow derived mesenchymal stem cells (MSCs) have been shown to become hypertrophic and undergo endochondral ossification when implanted in vivo. Modulating this endochondral phenotype may be an attractive approach to engineering the osseous phase of an osteochondral implant. The objective of this study was to engineer an osteochondral tissue by promoting endochondral ossification in one layer of a bi-layered construct and stable cartilage in the other. The top-half of bi-layered agarose hydrogels were seeded with culture expanded chondrocytes (termed chondral layer) and the bottom half of the bi-layered agarose hydrogels with MSCs (termed osseous layer). Constructs were cultured in a chondrogenic medium for 21 days and thereafter were either maintained in a chondrogenic medium, transferred to a hypertrophic medium, or implanted subcutaneously into nude mice. This structured chondrogenic bi-layered co-culture was found to enhance chondrogenesis in the chondral layer, appearing to help re-establish the chondrogenic phenotype that is lost in chondrocytes during monolayer expansion. Furthermore, the bilayered co-culture appeared to suppress hypertrophy and mineralisation in the osseous layer. The addition of hypertrophic factors to the media was found to induce mineralisation of the osseous layer in vitro. A similar result was observed in vivo where endochondral ossification was restricted to the osseous layer of the construct leading to the development of an osteochondral tissue. This novel approach represents a potential new treatment strategy for the repair of osteochondral defects.
PUBLISHED
Keywords: Chondrocyte; msc; co-culture; hydrogel; osteochondral tissue engineering; endochondral.; Chondrocyte; msc; co-culture; hydrogel; osteochondral tissue engineering; endochondral.; Next Generation Medical Devices